[Rezension von: Lloyd, Dana, ca. 20./21. Jh., Land is kin : sovereignty, religious freedom, and indigenous sacred sites] - Shrubsole, Nicholas (A journal of church and state, 2025)
While many have offered commentary on Lyng v. Northwest Indian Cemetery Protection Association over the years, Land is Kin challenges us to reconsider the